Relationship between Social Support and Physical Exercise Adherence: A Systematic Review - YuBin Yuan; Roxana Dev Omar Dev; Kim Geok Soh; XueYanJi; Qi Guo, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
In general, it is recommended by the World Health Organisation that individuals engage in at least sixty minutes of physical exercise. However, the guidelines or daily minimum required physical activities for adolescents necessitate substantial support. The study aims to explore the various sources of support and the relationship between adolescents' social support and physical activity adherence in their daily lives. This study utilised a systematic review of five major databases, without any time restrictions, and without limiting the geographical scope. The PRISMA technique was employed, resulting in the inclusion of approximately 86 publications that met the criteria. The studies revealed that parents, family, peers, friends, and teachers play a crucial role in providing social support. Irrespective of the sources of social support, there is a range of effects and relationships between social support and physical activity in adolescents, which can vary from positive to negative. Therefore, certain research studies suggest that encouraging adolescents or children to engage in physical exercise may result in them resisting the pressure and exhibiting lower levels of activity. Thus, fostering knowledge and promoting awareness about health can help adolescents engage in physical activity.